From Sources to Repertoires: Graecisms in Gabriele D'Annunzio's Poetic Work (Altre Modernità, 2025)
For a long time, Dance Studies has focused on the analysis of choreographic manifestations primarily through historical and documentary methodologies, limiting its research horizon to what is considered the ‘repertoire’. The term itself is commonly associated with a museum-like and conservative meaning, whereas in its very root, ‘reperio’, emerges the dynamic nature of discovery and a prolific inclination towards innovation. In dance, the repertoire consists of those scenic forms (from Ballet d'action to 19th century Romantic ballet to 20th century neoclassical and modernist forms) that have been formalized through techniques, styles, and notation systems. In recent years, new generations of artists have embarked on a path of rediscovery of these works, highlighting their cultural components, their gestural forms and their historical value, not with reconstructive or modernising purposes, but to delve into the nature of bodies as repositories of iconographic schêmata and cultural inheritances transmitted across the ages. These bodies are thus an archive, a place of “sedimentation of traces” (Giannasca 342). In this paper, we explore the relationship between dance and repertoire through selected case studies from recent Italian productions: Salvo Lombardo's Excelsior and Collettivo Cinetico's Sylphidarium, observing more broadly how the repertoire is an organism in the making, useful for processes of rewriting and memory.
Keywords: Graecisms; D’Annunzio; lexicon; poetry